2021
DOI: 10.1002/pc.25954
|View full text |Cite
|
Sign up to set email alerts
|

Crashworthiness analysis of perforated metal/composite thin‐walled structures under axial and oblique loading

Abstract: As a kind of lightweight structure with great economic benefits, metal/composite hybrid structure is raising rapidly among automobile safety components due to its excellent anti-collision performance. In this paper, a new design was developed by introducing an induced circular hole to improve the energy absorption performance of the AL/CFRP hybrid thin-walled tubes under different loading conditions. Quasi-static experiments and finite element simulation were carried out on the hybrid tubular sample with induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…As a kind of lightweight structures with great economic benefits, metal/composite hybrid structures are rapidly used as automobile safety components due to its excellent anticollision performance. [ 15 ] Extensive research works have been conducted on metal/composite hybrid structures. [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a kind of lightweight structures with great economic benefits, metal/composite hybrid structures are rapidly used as automobile safety components due to its excellent anticollision performance. [ 15 ] Extensive research works have been conducted on metal/composite hybrid structures. [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Fip falls by 24.32% and SEA slightly rises by 0.68% as compared to the intact tube. Fan et al [ 15 ] showed that the induction of holes can effectively reduce Fip and improve U of Al/CFRP thin‐walled tubes subjected to axial loading. The effect of increasing d on U is less than that of increasing N.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of CFRP are different according to the ply thickness, angle, and order. [23,24] For CFRP parts, using the whole ply will lead to material waste. Therefore, according to the requirements of working conditions, optimizing the composite laminate of CFRP can get different ply areas, which makes the requirements of stiffness and strength larger.…”
Section: Optimization Design Of Cfrp Oil Panmentioning
confidence: 99%
“…[9] The reason behind the diverse applications of these composites is the excellent thermo-mechanical properties like high strength, elevated deterioration resistance, resistance to high temperature and high levels of hardness. [10][11][12] Due to the isotropic nature of nanoparticles of metals with refined physical and chemical properties, [13] MMCs are fabricated with the addition of nanoparticle metals. The nanoparticles are those particles whose size is within the scale of 1 Â 10 À9 meters to 100 Â 10 À9 m. [14,15] The property of nanoparticles whether physical or chemical is dependent on the size [16] as well as the shape of the particle.…”
mentioning
confidence: 99%